Effect of protein source and nonroughage NDF content in finishing diets of feedlot cattle fed free-choice hay on growth performance and carcass characteristics. Issue 4 (4th December 2021) - Pittaluga, Alejandro M; Clark, Chris; Relling, Alejandro E
Abstract: One-hundred twenty crossbreed steers (initial body weight (BW) 566 ± 42 kg) were used to evaluate the interaction of protein source (PS) and nonroughage NDF content (NRFC) in finishing diets of feedlot cattle fed free-choice hay on performance and carcass characteristics. Steers were stratified by BW and randomly assigned to 8 pens (2 × 2 factorial) and fed for 104 ± 10 d. Four dietary treatments were investigated: (1) distillers' dry grains with solubles (DDGS) and a low NRFC (DLF), (2) DDGS and a high NRFC (DHF), (3) soybean meal (SBM) and a low NRFC (SLF), (4) SBM and a high NRFC (SHF). Free-choice grass hay and concentrates were offered in a different bunk. Data were analyzed as a randomized complete block design. Do to the confounded effect of PS and protein intake, a linear regression was used to evaluate the effect of protein intake in growth performance. For gain to feed ratio (G:F) an interaction tended to occur ( P = 0.10) between PS and NRFC. Steers on the DHF treatment had a lower G:F compared with SLF and SHF. Feeding SBM increased ( P = 0.05) final BW, tended to increase ( P = 0.06) average daily gain (ADG), and decreased ( P = 0.05) hay intake (HI) compared with steers fed DDGS. There was a positive association ( P ˂ 0.01) of crude protein intake with ADG and FBW. Dietary NRFC did not change ( P ≥ 0.3) final BW, ADG, DMI, and HI. Protein source did not affect ( P ≥ 0.16) hot carcass weight (HCW), longissimus muscle (LM) area, dressing, 12th rib fat thickness, or marbling score (MS). No differences were detected between NRFC for dressing, HCW, LM area, or MS ( P ≥ 0.18); but diets with greater NRFC decreased ( P = 0.03) the 12th rib fat thickness. Steers in the SHF treatment presented the lesser kidney-pelvic-heart fat compared with the remaining treatments (PS × NRFC interaction, P = 0.04). Soybean meal inclusion/increase in protein intake improved growth performance of feedlot steers compared with DDGS, despite protein intake meet the protein requirement. Increasing the NRFC did not affect growth or HI but decreased feed efficiency of steers fed DDGS.